MODEL PENGUKURAN KINERJA INSTANSI PEMERINTAH PADA KANTOR KECAMATAN TUTUR KABUPATEN PASURUAN - Khumaidi khumadi; Melien Riska Yulia Sari (Universitas Halu Oleo, 2021)
The performance of government agencies must always be improved because it is in the public spotlight. The public wants a government to have a good performance in carrying out its duties and responsibilities in accordance with applicable laws. Human resources are a very influential factor in carrying out the performance of an agency. Improved performance of government agencies can be influenced by several factors. This study aims to determine employee operational audits and accountability in improving agency performance in Tutur District. The method used in this study is qualitative with descriptive analysis method. The object of this research is the Tutur District Office while the subjects of this study are the employees Tutur district. Data collection techniques in this study using trianguation techniques is observation, interviews and documentation. Data analysis techniques in this study are data collection, data reduction, data presentation and conclusions. The results of this study indicate that the performance of the Tutur District office has decreased, this is due to employee operations that are not appropriate and not in accordance with the conditions so that individual performance can not be maximized and also the value of accountability that does not meet the target.